STATE OF LAW, DEMOCRACY AND OLIGARKY IN INDONESIA - Ellydar Chaidir; Umi Muslikhah (International Conference On Law And Social Sciences, 2024)
The dynamics of democracy from the early era of independence to reform experienced ups and downs, the configuration of which was largely tied to the interests of certain elites, which later became known as oligarchy. A democratic rule of law is included as an ideal concept for implementing the protection of the interests of citizens' constitutional rights. This was then contained in the 4th paragraph of the 1945 Constitution of the Republic of Indonesia "... to protect the entire Indonesian nation and all of Indonesia's blood and to promote general welfare, educate the life of the nation and participate in world order.